Phenoxazine Derivatives Inactivate Human Cytomegalovirus, Herpes Simplex Virus-1, and Herpes Simplex Virus-2 In Vitro - Kyoko Hayashi; Toshimitsu Hayashi; Akio Tomoda (Elsevier, 2008)
We examined whether phenoxazine derivatives, 2-amino-4,4α-dihydro-4α-7-dimethyl-3H-phenoxazine-3-one (Phx-1), 3-amino-1,4α-dihydro-4α-8-dimethyl-2H-phenoxazine-2-one (Phx-2), and 2-amino-phenoxazine-3-one (Phx-3) may have antiviral activity against herpes family viruses: human cytomegalovirus (HCMV), herpes simplex virus type 1 (HSV-1), and herpes simplex virus type 2 (HSV-2). The antiviral activity was evaluated by the selectivity index (SI), which is the ratio of 50% cytotoxic concentration (CC50) and 50% antiviral concentration (IC50). Among these phenoxazines, Phx-2 exerted strong antiviral activity to HCMV with the SI of 200, while Phx-1 and Phx-3 exerted no marked anti-HCMV activity. Phx-2 also showed moderate inhibition of HSV-1 and HSV-2, with the SI of 6.7 and 17, respectively. In the time-of-addition experiments, inhibitory effect of Phx-2 against HCMV was active even when applied to cells at 100 h after HCMV infection, while ganciclovir (GCV) showed potent inhibition when applied to cells before 42-h post-infection, but its inhibitory effects disappeared thereafter. Attachment and penetration of HCMV was not affected by the presence of Phx-2. When HCMV was pretreated with Phx-2, concentration-dependent virucidal action was observed, suggesting that Phx-2 inactivates HCMV directly. From these data, it was found that Phx-2 might have a different anti-HCMV target from GCV. Keywords:: human cytomegalovirus, herpes simplex virus type 1, herpes simplex virus type 2, phenoxazine